Gerunds Found on the Scripts of “Thor” Movie - Karimah, Alfira Akhlaqul (English Language and Literature in Education Journal, 2024)
This research aimed to analyze the functions of gerunds in the subtitles of the movie “Thor”, focusing on the main character, Thor Odinson. A gerund is a verb ending in -ing that functions as a noun. This descriptive qualitative study analyzed phrases or sentences containing gerunds from the movie's subtitles. The instruments used were the researcher and an observation field note. Data analysis involved classification, description, and drawing conclusions, identifying three functions of gerunds: (1) as a subject, with one instance, (2) as a direct object, with eleven instances, and (3) as a subjective complement, with twenty-three instances. No instances of gerunds functioning as the object of a preposition were found. The findings contribute to a better understanding of gerund usage in cinematic language, providing valuable insights for language teaching, linguistic research, and translation studies. Educators can use movie subtitles to teach grammatical concepts, making lessons more engaging. This study also enriches research on gerunds, highlighting their functional distribution in subtitles, and offers guidance for subtitle translators to improve accuracy and coherence. Further research could explore gerund usage in various genres and contexts to enhance these implications.